2015
DOI: 10.5539/ass.v11n15p96
|View full text |Cite
|
Sign up to set email alerts
|

Iranian English as a Foreign Language (EFL) Learners’ Argumentative Writing Performance in Private Language Institutes

Abstract: Literature on Iranian English as a Foreign Language (EFL) learners' problems in their writing skills is lacking. The present study analyzes a group of Iranian EFL students' written samples to diagnose their main area(s) of difficulty in writing argumentative essays. For this purpose, a sample of 69 argumentative essays was collected. Two raters used an analytic argumentative writing scale to score the samples. Based on the scores assigned to their written samples, majority of these students indicated excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Many studies have also adopted a textual perspective and investigated the learners' difficulties with the argumentative writing from a textual perspective by analyzing the students' texts. These studies have shown that English argumentative writing poses rhetorical difficulties for the learners (Al-Abed-Al-Haq and Ahmed, 1994;Hemmati, 2001;Khiabani and Pourghassemian, 2009;Dastjerdi and Samian, 2011;Nimehchisalem et al, 2015;Abdollahzadeh et al, 2017;Saprina et al, 2020). In addition, text-based research that has compared argumentative writing by native and non-native English speakers reveals rhetorical and textual differences, although some similarities have also been found (Choi, 1986(Choi, , 1988aLux, 1991;Ferris, 1994;Bouchard, 1996;Kim, 1996;Hinkel, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have also adopted a textual perspective and investigated the learners' difficulties with the argumentative writing from a textual perspective by analyzing the students' texts. These studies have shown that English argumentative writing poses rhetorical difficulties for the learners (Al-Abed-Al-Haq and Ahmed, 1994;Hemmati, 2001;Khiabani and Pourghassemian, 2009;Dastjerdi and Samian, 2011;Nimehchisalem et al, 2015;Abdollahzadeh et al, 2017;Saprina et al, 2020). In addition, text-based research that has compared argumentative writing by native and non-native English speakers reveals rhetorical and textual differences, although some similarities have also been found (Choi, 1986(Choi, , 1988aLux, 1991;Ferris, 1994;Bouchard, 1996;Kim, 1996;Hinkel, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drawing on the related literature (Lea and Street, 1998;Nesi and Gardner, 2006;Qin and Karabacak, 2010;Wingate, 2012;Nimehchisalem et al, 2015;Abdollahzadeh et al, 2017;Altınmakas and Bayyurt, 2019) and the researcher's personal experiences with teaching undergraduate writing courses, the researcher developed an open-ended questionnaire in order to elicit the perceptions of the students with regard to argumentative essays (Supplementary Appendix III). The questionnaire included close-response items about the students' background including demographic information and English essay writing experiences.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Argumentative writing is one of the most significant types of writing for students in higher education so much so that Crowhurst (1990) related academic successes to the degree of argumentative writing skill among students; therefore, argumentative writing has been the subject of extensive research (e.g., Chapple & Curtis, 2000;Ferretti, Lewis, & Andrews-Weckerly, 2009;Lea & Street, 1998;Nimehchisalem, Abbasi, Ebrahimzadeh, & Kalajahi, 2015;Nussbaum, 2008). The results of these studies have perpetuated various aspects of this multifarious writing skill.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the number of studies dealing with argumentative writing in Iran are so scant that one cannot draw a conclusion about the effectiveness of argumentative writing instruction in Iran. The few studies that have focused on argumentative writing in Iran (e.g., Nimehchisalem et al, 2015) report that Iranian EFL learners do not have sufficient argumentative writing skills. In addition, as reported by Ketabi and Torabi (2017) writing is among the last skills which are dealt with in classes, and this reduces the language learners' writing skills.…”
Section: Introductionmentioning
confidence: 99%